2017
DOI: 10.1177/0022042617731338
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Cigarette Use Trends in the United States among Multiracial and Other Youth, 1994-2008

Abstract: Tobacco use among the multiracial population is grossly underresearched. This study explored the cigarette-smoking trends of multiracial individuals over time in comparison with monoracial individuals and assessed the relationship between cigarette smoking and factors at the individual, family, peer, school, and state levels. This study used data collected by the National Longitudinal Study of Adolescents and Adult Health from 1994 to 2008. This study examined a subsample of 9,421 respondents who self-identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…While, using of drugs was approximately (22.5%) between students in Mosul university. This study similar with (16) he stated the using Smoking during adolescence is one of the strongest predictors of incessant smoking patterns constituted of (57%).On the other hand , this result is consistent with the study in Baghdad , ( 2010) found that lifetime prevalence of alcohol use in Baghdad was 17.8% and drug use prevalence was 7.02% (17) .These increases in the use of alcohol, prescription drugs, and illicit drugs may indicate an increase in substance use disorders in the country and, therefore, an increased need for treatment interventions. This table (3) shows that the majority of participants in study were upper lower class according to Kuppuswamy's scale approximately (45%).While, lower class about (11.25%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While, using of drugs was approximately (22.5%) between students in Mosul university. This study similar with (16) he stated the using Smoking during adolescence is one of the strongest predictors of incessant smoking patterns constituted of (57%).On the other hand , this result is consistent with the study in Baghdad , ( 2010) found that lifetime prevalence of alcohol use in Baghdad was 17.8% and drug use prevalence was 7.02% (17) .These increases in the use of alcohol, prescription drugs, and illicit drugs may indicate an increase in substance use disorders in the country and, therefore, an increased need for treatment interventions. This table (3) shows that the majority of participants in study were upper lower class according to Kuppuswamy's scale approximately (45%).While, lower class about (11.25%).…”
Section: Discussionsupporting
confidence: 89%
“…F: Frequency, %: Percent, χ 2 : Chi-square, all group differences p > 0.05, types of study reported by Total score distributes according kuppuswamy's; upper class(26-29);upper middle class(16)(17)(18)(19)(20)(21)(22)(23)(24)(25);lower middle class…”
mentioning
confidence: 99%
“…More than 480,000 deaths per year can be still attributed to cigarette smoking and secondhand smoke exposure [ 2 ]. The prevalence of tobacco use is increasing in some age and racial/ethnic subgroups [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the current population in Oman is young [7]. Studies all over the world have shown youth to be at a higher risk for non-medical use of substances compared to the rest of the population [8, 9,10]. There is an abundance of literature suggesting that youth choosing to experiment with psychoactive substances earlier are likely to face more difficulties in engaging with their lives in a meaningful manner [11, 12,13].…”
Section: Introductionmentioning
confidence: 99%